Evaluasi Kualitas Website Prasetya Online Universitas Brawijaya menggunakan Metode Webqual 4.0 Modifikasi dan Importance Performance Analysis (IPA) - Nur Amalia Kusumawati; Yusi Tyroni Mursityo; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Prasetya Online UB is a website owned by Brawijaya University which provides information and news about Universitas Brawijaya. Based on the experience of students as website users, students assess the quality of the website is still not good in terms of appearance to the services provided. In addition, there has never been an evaluation regarding the quality of a website based on user perceptions. This study aims to assess the quality of the website according to user perceptions by using the Webqual 4.0 method which has 4 dimensions, namely usability, information quality, service interaction quality, and user interface quality, while the Importance Performance Analysis (IPA) method is used to determine the indicators contained. in Webqual 4.0 Mods that require improvement. The research data was obtained by distributing questionnaires online to 100 Brawijaya University students who have experience using the website. The results showed that the website was of poor quality and did not meet user expectations. There are 4 indicators that are the main priority for improvement, namely appearance, timeliness of information, functioning website links, ease of communication with managers. In addition, there are 2 indicators that are low priority for improvement, namely a display that matches the type of news website and the layout of the information. Other indicators do not have priority improvements because their performance scores are good and sufficient to be maintained. Recommendations for improvement are focused on indicators that are in the top and low priority and refer to WCAG 2.0